Differentiation of Workers’ Primary and Secondary Identity in the Small Enterprises in Poland - Zawadzki, Kamil; Wojdyło, Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article analyzes the differentiation of selected characteristics of the primary identity (age, sex) and the secondary identity (education, professional experience) of workers employed in the small enterprises in Poland. We extracted data on over 146 thousands workers employed in 7,2 thousands small enterprises out of the individual data base Z–12 (report on structure of wages by occupations). The research shows that within small businesses in Poland the identity of workers varies considerably, especially as regards the secondary one. That diversity is significantly differentiated accordingly to the size and the industry of the employer. Identified instruments of diversity management may help to optimize the human capital also in the small businesses in Poland.